Clinical epidemiology of peritoneal metastases in China: The construction of professional peritoneal metastases treatment centers based on the prevalence rate. Issue 1 (January 2023) - Yang, Rui; Su, Yan-dong; Ma, Ru; Li, Yan
Abstract: Objective: To understand the tumor burden of peritoneal metastases (PM) in China, and to guide the construction of professional PM treatment centers in China. Methods: Based on the cancer statistics by the National Cancer Center of China published in 2016, the prevalence of PM in 2020 was calculated according to the population statistics in China and the survival and mortality rates of various PM. Results: The prevalence rates of PM in China were as follows: gastric cancer PM 371.0/million, absolute number 523, 937; colorectal cancer PM 47.1/million, absolute number 66, 482; ovarian cancer PM 97.1/million, absolute number 137, 083; pseudomyxoma peritonei 25.1/million, absolute number 35, 425; malignant peritoneal mesothelioma 2.6/million, absolute number 3737; the above total was 766, 664. According to the annual high-quality treatment volume of 365 cases in each professional PM treatment center, China needs to establish 1194 specialized PM treatment centers. At present, there are 1580 tertiary first-class hospitals in China. Therefore, for every 3 first-class tertiary hospitals in China there should be at least 2 PM treatment centers in full operation. Conclusions: Considering the large number of PM patients in China and the relatively small number of professional PM treatment centers, more resources should be devoted to the promotion and construction of PM treatment centers.